2006
DOI: 10.1002/jhm.71
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reliance on CT pulmonary angiography on diagnosis of pulmonary embolism: A Bayesian analysis

Abstract: BACKGROUNDSpiral computed tomographic pulmonary angiography (CTPA) has become the primary test used to investigate suspected pulmonary embolism (PE) at many institutions, despite uncertainty regarding its sensitivity and specificity. Although CTPA‐based diagnostic algorithms focus on minimizing the false‐negative rate, we hypothesized that increasing use of CTPA also might lead to false‐positive diagnoses.OBJECTIVEDetermine the frequency of possible false‐positive diagnoses of PE when CTPA is the primary diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…We calculated the Wells score retrospectively as was previously done in studies by Chagnon et al, 11 Righini et al, 14 and Ranji et al 27 (although the methods used in these studies were not described in detail). We assumed that whenever a d-dimer test was ordered the treating physician thought that PE was less likely than an alternate diagnosis reasoning that, if they thought PE were the most likely diagnosis, ddimers should not have been obtained as, in this circumstance, they are not recommended as part of the diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the Wells score retrospectively as was previously done in studies by Chagnon et al, 11 Righini et al, 14 and Ranji et al 27 (although the methods used in these studies were not described in detail). We assumed that whenever a d-dimer test was ordered the treating physician thought that PE was less likely than an alternate diagnosis reasoning that, if they thought PE were the most likely diagnosis, ddimers should not have been obtained as, in this circumstance, they are not recommended as part of the diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…CTPA is more sensitive for differentiation because it shows the positions of vein stenosis and pulmonary embolus separately. [2][3][4]13 However, with our patient the massive filling defect on CTPA misled the clinicians and radiologists to the misdiagnosis of pulmonary embolism. Actually, pulmonary-vein stenosis triggers pulmonary congestion, increases the capillary wedge pressure, and ultimately slows the pulmonary arterial flow.…”
Section: Discussionmentioning
confidence: 70%
“…7,8 However, reliance on CTPA and V /Q scan alone can lead to a falsepositive diagnosis of pulmonary embolism. 4 This teaching case is an example in point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many practitioners fail to realize the limitations of imaging tests, leading to both overdiagnosis and a delay in treatment, particularly when there is discordance between clinical pretest likelihood and the imaging result. Indeed, among a cohort of 322 patients with a varying pretest likelihood of PE, Ranji et al demonstrated a 25% false-positive rate for CTPA even under optimistic assumptions of accuracy (18). Accordingly, there is a need for newer imaging modalities with higher accuracy and reproducibility.…”
Section: Discussionmentioning
confidence: 99%